2015
DOI: 10.2217/pgs.15.132
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 Gln11Leu Single Nucleotide Polymorphism and Response to Treatment with Imiquimod in Patients with Basal Cell Carcinoma: A Pilot Study

Abstract: The results of this study show that patients carrying at least one T allele of the TLR7 promoter polymorphism are associated with an increased probability to be resistant to imiquimod therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In one published study, the relation between a promoter TRL7 gene SNP (rs179008; not investigated in present study) and response to imiquimod (TLR7 agonist) was explored in cutaneous basal cell carcinoma patients. The results demonstrated that patients carrying at least one SNP allele (T allele) are at an increased risk to be resistant to such therapy [32]. Therefore, TLR7 gene may harbor important functional SNPs that not just influence susceptibility to malignancies, but may also influence response to therapies.…”
Section: Discussionmentioning
confidence: 98%
“…In one published study, the relation between a promoter TRL7 gene SNP (rs179008; not investigated in present study) and response to imiquimod (TLR7 agonist) was explored in cutaneous basal cell carcinoma patients. The results demonstrated that patients carrying at least one SNP allele (T allele) are at an increased risk to be resistant to such therapy [32]. Therefore, TLR7 gene may harbor important functional SNPs that not just influence susceptibility to malignancies, but may also influence response to therapies.…”
Section: Discussionmentioning
confidence: 98%
“…Recent and upcoming investigations on targeting Hp signaling in tumors should concentrate on strategies addressing and exceeding resistance mechanisms. The design and development of new generation therapeutics should take into account both downstream genetic variants, such as GLI gain-of-function and SUFU loss-of-function mutations, and acquired SMO mutations [ 45 , 46 ]. In a recent proof of concept, we speculated on the association of, itraconazole, arsenic trioxide, all-trans-retinoic acid and nicotinamide combined with conventionalHp inhibitors to carry out the therapeutic response, prevent tumor resistance and diminish the dosage of each drug and associated AE [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the TLR3 and 7 polymorphisms and their correlations with human and mouse susceptibility to viral infections, we propose that avian TLR3 and 7 differences may be associated with either resistance or susceptibility to avian infectious diseases (Schott et al, 2007;Lee et al, 2013;Piaserico et al, 2015;He et al, 2017). This study may be helpful to further understand the varied resistance to viral diseases that exist between different avian species.…”
Section: Identification Of Avian Toll-like Receptor 3 and 7 And Analy...mentioning
confidence: 95%